Strategi Meningkatkan Kesiapan Guru dalam Implementasi Kurikulum Merdeka di SDN Pelambuan 2 - Muhammad Hafi Badali; Ahya Nabila; Diani Ayu Pratiwi; Aslamiah .; Chintya Adelya; Syaidati Elida (CV. ITTC INDONESIA, 2025)
This study investigates strategic efforts to enhance teacher readiness in the implementation of the Merdeka Curriculum at SDN Pelambuan 2. Despite ongoing adoption, effective curriculum implementation remains challenged by limited pedagogical knowledge and the necessity for continuous professional development, particularly in the domain of digital literacy integration. Employing a qualitative descriptive approach, the research involved two educators as primary informants. The findings reveal a high degree of institutional readiness, characterized by the establishment of professional learning communities, the effective utilization of the PMM and GTK platforms, and strong administrative support from the school leadership. These results underscore the school’s institutional commitment and capacity to effectively operationalize the Merdeka Curriculum.